Fiscal Policy and Investment as Determinants of Regional Economic Resilience In Indonesia - Nurnaningsih Nurnaningsih; Patta Tope; Suparman Suparman; Yunus Sading (Journal of Economic Education and Entrepreneurship Studies, 2026)
Economic resilience has been a major concern in economic development studies, especially when there are recurrent macroeconomic shocks and structural vulnerabilities. Although fiscal and investment policies are widely recognized as drivers of economic growth, empirical evidence linking fiscal and investment policies to regional economic resilience from an aggregate demand perspective is limited. This study examines the impact of these two variables on economic resilience in 34 provinces in Indonesia during the period 2012-2024. Regional resilience is measured using real aggregate consumption relative to counterfactual long-term trends, thereby capturing the capacity of regions to withstand shocks and recover over time. The analysis used a Fixed Effects panel model, selected based on the Chow and Hausman tests. The findings show that disaster-related spending through contingency significantly increases the region's economic resilience in the short term, while capital expenditure also has a positive short-term effect, albeit on a smaller scale. In addition, foreign direct investment and domestic investment show statistically significant and consistent positive effects on economic resilience. These results extend Keynesian aggregate demand theory by showing that fiscal and investment policy instruments not only stabilize output but also strengthen adaptive regional resilience, offering important policy insights for disaster-prone developing countries.